CIRCUITS CONTROLLER ROOM USING LIGHT INFRA RED SENSOR BASED MICROCONTROLLER AT89C51 - Cipto Winarno; Aqwam Rosadi Kardian., SKom., MM (Jurnal Sistem Komputer, 2008)
The writing of this research create a system that can control lights in the room from adistance by using infrared transmission media to be integrated starting from theinfrared transmitter, infrared receiver, microcontroller AT89C51 and lights the room.The maximum distance that can be achieved by infrared sensors of infraredtransmitter approximately 10 meters far. Light-emitting diode (LED) as a source ofinfrared light to transmit data and a series of infrared receiver used as a recipientphotodioda emitted by infrared.